Pengaruh Self Image terhadap Kemampuan Public Speaking Siswa di Pondok Pesantren Tarbiyah Islamiyah Koto Tinggi Pandai Sikek - Rizal, M.; Yusri, Fadhilla (Asian Journal of Islamic Studies and Da'wah, 2024)
This research aims to see how much influence self-image has on students' public speaking abilities at the Tarbiyah Islamiyah Koto Tinggi Pandai Sikek Islamic Boarding School. The population in this study was 174 people. The research sample consisted of 43 people using stratified random sampling techniques. The results of this research show that the regression results are negative (-), namely Ῠ = -18.582 + 1.281X. The meaning of this number is that if self image (X) then the constant value of public speaking (Y) is -18.582, and for every 1% increase in the value of self image, the value of public speaking increases by 1.281. The results of hypothesis testing in this study obtained a large F count from Ftable (40.940>4.07) that Ho was rejected while Ha was accepted, meaning that there is a significant influence between self image on students' public speaking abilities at the Tarbiyah Islamiyah Koto Tinggi Pandai Sikek Islamic Boarding School. The large influence of self-image on students' public speaking abilities at the Tarbiyah Islamiyah Koto Tinggi Pandai Sikek Islamic Boarding School can be seen from the results of the coefficient of determination obtained at 0.500, this means that 50% of self-image influences public speaking and 50% is influenced by other external factors. research variable.